A comprehensive influenza reporter virus panel for high-throughput deep profiling of neutralizing antibodies - Creanga, Adrian; Gillespie, Rebecca A.; Fisher, Brian E.; Andrews, Sarah F.; Lederhofer, Julia; Yap, Christina; Hatch, Liam; Stephens, Tyler; Tsybovsky, Yaroslav; Crank, Michelle C.; Ledgerwood, Julie E.; McDermott, Adrian B.; et al. (Nature communications, 2021)
Broadly neutralizing antibodies (bnAbs) have been developed as potential countermeasures for seasonal and pandemic influenza. Deep characterization of these bnAbs and polyclonal sera provides pivotal understanding for influenza immunity and informs effective vaccine design. However, conventional virus neutralization assays require high-containment laboratories and are difficult to standardize and roboticize. Here, we build a panel of engineered influenza viruses carrying a reporter gene to replace an essential viral gene, and develop an assay using the panel for in-depth profiling of neutralizing antibodies. Replication of these viruses is restricted to cells expressing the missing viral gene, allowing it to be manipulated in a biosafety level 2 environment. We generate the neutralization profile of 24 bnAbs using a 55-virus panel encompassing the near-complete diversity of human H1N1 and H3N2, as well as pandemic subtype viruses. Our system offers in-depth profiling of influenza immunity, including the antibodies against the hemagglutinin stem, a major target of universal influenza vaccines. Understanding the human antibody response to influenza A virus strains is important for vaccine development. Here, Creanga et al. generate a panel of 55 replication-deficient reporter viruses representing diversity of human H1N1 and H3N2, and pandemic subtypes and characterize the neutralization profile of 24 antibodies and polyclonal sera.